Análisis técnico-económico de las actividades de bacheo para la conservación Vial en Costa Rica - Fonseca-Duarte, José Rodolfo (Instituto Tecnológico de Costa Rica, 2012)
This project responds to the necessity for the use of new materials to the tendering procedures, so actuality there is a register by the CONAVI, the use of hot mix asphalt (HMA). Actually there is not a quantitative damage records to allow determinate the best way which areas have been taken part by patching methods. The project is divided in three principal parts: the first consists to determinate the damages on pavement surface (rigid or flexible). The second is an economic analysis for the use of new materials, and the last is about technical comparison of actual patching activities used. The tool used to determinate of damages was based in SIECA’s manuals, and was complemented with other documents of organizations to take charge of pavement maintenance. When the tool was developed, it was used to take the damage of the rigid and flexible selected sections for the 1-7, Cartago conservation zone. The materials that analyzed as a possibility of usage for patching activities were: warm mix asphalt, cold-mix asphalt, rolled compacted concrete (RCC) and high initial resistance concrete (Fast-Track); taking as a price reference HMA patching activities. From the materials used, was found that the price of cold-mix asphalt less expensive than the HMA. But the patches made with cold-mix asphalt could have less duration than the HMA’s patches according to the experts say. Another material to consider for patching is the RCC, because it presents an considerable save for the companies. Finally was effected a comparative analysis referring to manner of execution for the patching activities with the actual manual’s specifications of the country, and given satisfactory results.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: Mezcla Asfáltica en frío; Mezcla Asfáltica en Caliente; Mezcla Asfáltica en Tibio; CCR; Concreto Fast-Track